Negotiating normativities: Counter narratives of lesbian queer world making in Cape Town - Holland-Muter, Susan (Department of Sociology, 2018)
This thesis explores the different modes and meanings of queer world making (QWM) of lesbians in Cape Town. Through an analysis of in depth interviews and focus groups it reveals lesbians' constructions of their intersectional and permeable QWM through a series of counter narratives enacted in three interconnected socialities. Generational narratives reveal psycho-social processes of recognition of lesbian desire and coming into a lesbian subjectivity in a range of modes of QWM. Lesbian erotic world making centres their entitlement to enact sexual autonomy and sexual pleasure. Their counter narratives reveal how they simultaneously inhabit and extend normative gender regimes. Their productions of desire reveal a lesbian centred frame of sexual pleasure that extends the erotogenic body beyond the genitalia, innovates and transforms hegemonic libidinal zones, and extends phallocentric culture. Lesbian motherhood as a site of QWM reveals the participants' negotiations, conflict, stress and agency in relation to the 'good mother' discourse that undergirds mothering practices in South Africa. Their counter narratives reveal how they simultaneously resist and re-inscribe heteronormativity in their motherhood practice. Ironically, it is through publicly assuming their sexuality that they are they able to perform 'good motherhood'. They perform private resistance and public complicity with good mother ideologies; and simultaneously centre and destabilize the role of the father. They manage their 'difference' to the heterosexual norm by providing their children with tools to navigate heteronormativity, while simultaneously claiming being an unexceptional family. Their queer place making strategies in everyday spaces in Cape Town demonstrate how they rework racialised notions of belonging to incorporate the queer body (at times ephemerally) to make Cape Town home. Their creation of lesbian social networks and communities, embodied in lesbian social scenes and within their private homes, reveals how Cape Town is experienced as a hybrid space, their contrasting and competing narratives of the city revealing narratives of fractured belonging. QWM reveals how lesbians resist and (re)shape hegemonic identities, discourses and practices, revealing 'a mode of being in the world that is also inventing the world' (Muñoz, 1999: 121). QWM is about borderlands (Anzaldúa, 1987), where one lives within the possibility of multiple plotlines (Clandinin & Rosiek, 2006). Their queer life worlds are permeable to racialised heteronormativities. But their agency reveals multi-vocal and multivalent queer life worlds, enmeshed in the web of racialised, gendered, sexualised, aged and class-based hierarchies in Cape Town. There is no singular way of doing a lesbian subjectivity, no singular utopian notion of a lesbian community. Their differences are located in their varying political perspectives and their social positionalities of privilege and penalty, in short, how they position themselves within the 'politics of belonging' (Yuval Davis, 2006).